The Future Ed Project: New Business Models For United States And Global Legal Education - Conference Report (Amsterdam Law Forum, 2010)
Got an idea about the future of legal education? Think it’s time to go clinical? Or global? Or virtual? Should law be combined with other fields of study at the graduate or undergraduate level?